Altered Expression Profile of Renal α1D-Adrenergic Receptor in Diabetes and Its Modulation by PPAR Agonists - Xueying Zhao; Yuanyuan Zhang; Michelle Leander; Lingyun Li; Guoshen Wang; Nerimiah Emmett (Journal of Diabetes Research)
Alpha1D-adrenergic receptor (α1D-AR) plays important roles in regulating physiological and pathological responses mediated by catecholamines, particularly in the cardiovascular and urinary systems. The present study was designed to investigate the expression profile of α1D-AR in the diabetic kidneys and its modulation by activation of peroxisome proliferator-activated receptors (PPARs). 12-week-old Zucker lean (ZL) and Zucker diabetic fatty (ZD) rats were treated with fenofibrate or rosiglitazone for 8–10 weeks. Gene microarray, real-time PCR, and confocal immunofluorescence microscopy were performed to assess mRNA and protein expression of α1D-AR in rat kidney tissue. Using microarray, we found that α1D-AR gene was dramatically upregulated in 22-week-old ZD rats compared to ZL controls. Quantitative PCR analysis verified a 16-fold increase in α1D-AR mRNA in renal cortex from ZD animals compared to normal controls. Chronic treatment with fenofibrate or rosiglitazone reduced renal cortical α1D-AR gene. Immunofluorescence staining confirmed that α1D-AR protein was induced in the glomeruli and tubules of diabetic rats. Moreover, dual immunostaining for α1D-AR and kidney injury molecule-1 indicated that α1D-AR was expressed in dedifferentiated proximal tubules of diabetic Zucker rats. Taken together, our results show that α1D-AR expression is upregulated in the diabetic kidneys. PPAR activation suppressed renal expression of α1D-AR in diabetic nephropathy.